2018
DOI: 10.5194/amt-11-1143-2018
|View full text |Cite
|
Sign up to set email alerts
|

Water vapour retrieval using the Precision Solar Spectroradiometer

Abstract: Abstract. The Precision Solar Spectroradiometer (PSR) is a new spectroradiometer developed at PhysikalischMeteorologisches Observatorium Davos -World Radiation Center (PMOD-WRC), Davos, measuring direct solar irradiance at the surface, in the 300-1020 nm spectral range and at high temporal resolution. The purpose of this work is to investigate the instrument's potential to retrieve integrated water vapour (IWV) using its spectral measurements. Two different approaches were developed in order to retrieve IWV: t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…where u H 2 O is the column water vapour content (precipitable water) taken from a global navigation satellite system (GNSS) receiver that considers satellite precise orbits at IZO (Romero Campos et al, 2009); A H 2 O is the spectral absorption coefficient (Rothman et al, 2013); and the b H 2 O exponent depends on the central wavelength position, instrument filter function, as well as the atmosphere pressure and temperature (Halthore et al, 1997). We have determined τ H 2 O (λ) from the transmittance for different water vapour and solar zenith angle (SZA) values from the MODerate resolution atmospheric TRANsmission (MODTRAN) model (Raptis et al, 2018).…”
Section: Spectral Langley Calibrationmentioning
confidence: 99%
See 2 more Smart Citations
“…where u H 2 O is the column water vapour content (precipitable water) taken from a global navigation satellite system (GNSS) receiver that considers satellite precise orbits at IZO (Romero Campos et al, 2009); A H 2 O is the spectral absorption coefficient (Rothman et al, 2013); and the b H 2 O exponent depends on the central wavelength position, instrument filter function, as well as the atmosphere pressure and temperature (Halthore et al, 1997). We have determined τ H 2 O (λ) from the transmittance for different water vapour and solar zenith angle (SZA) values from the MODerate resolution atmospheric TRANsmission (MODTRAN) model (Raptis et al, 2018).…”
Section: Spectral Langley Calibrationmentioning
confidence: 99%
“…Cachorro et al (2009) compared the AOD retrievals from LI-COR and a sun photometer and found AOD differences within 0.02 in the range of 440-1200 nm. Kazadzis et al (2018a) presented the results from the fourth WMO filter radiometer comparison for AOD measurements and found an excellent agreement at 500 and 865 nm between the Precision Solar Spectroradiometer (PSR; Raptis et al, 2018), Precision Filter Radiometer (PFR; Wehrli, 2008), and overestimation from 0.01 to 0.03 respectively. López-Solano et al (2018) compared AOD retrievals from Brewer spectrophotometers, AERONET-Cimel, and UV-PFR in the range of 300-320 nm at the Izaña Atmospheric Observatory, with uncertainties lower than 0.05.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…receiver considering satellite precise orbits at IZO (Romero Campos et al, 2009), A H 2 O the spectral absorption coefficient Rothman et al (2013), and the b exponent depends on the central wavelength position, instrument filter function, as well as the atmosphere pressure and temperature (Halthore et al, 1997). We have determined τ H 2O (λ) from the transmittance for different water vapour and solar zenith angle (SZA) values from the MODTRAN model (Raptis et al, 2018).…”
Section: Spectral Langley Calibrationmentioning
confidence: 99%
“…From the ground the most common ones include the GPS system (Mears et al, 2015), microwave radiometers (Westwater and Guiraud, 1980), Cimel sunphotometers (Halthore et al, 1997;Holben et al, 1998), FTIR (Sussmann et al, 2009) and Raman lidars (Ferrare et al, 1995;Filioglou et al, 2017). Recently, techniques have been developed for the retrieval of TPW from measurements of the precision solar spectroradiometer at World Radiation Center (WRC) Davos (Raptis et al, 2018), the PESR/PREDE-POM sun-sky radiometers (Campanelli et al, 2018) and from Max-DOAS observations (Wagner et al, 2013).…”
mentioning
confidence: 99%